Achievement of Product Quality by Using Organizational Agility Case Study In Numan Public Company - الرحيم, اياد محمود; اندراوس, رفل سعيد (Journal of Economics and Administrative Sciences, 2017)
Helps to use the mechanics of organizational agility in improving product quality by reducing waste or reduce it by removing activities that do not add value, which is the main reason for inefficiency and low productivity and increase costs, so the difficulty of changing administrative decisions to cope with internal and external changes to keep up with market trends renewable are the basic issue that research seeks to be addressed through the adoption of mechanisms of organizational agility, which will be reflected in bottom line in a positive way in improving the quality of products, and thus lies Applied important to look at the light of the results achieved and in which they can know the nature of the relationship between the current research variables, which help to find ways to increase the perception in the importance of the mechanics of the organizational agility and that lead to the improvement of the quality of products, as the aim of the research to develop the mechanics are relatively specific measures to cope with internal and external changes in the company researched and applied research in Numan public company and was named the plastics industry section of a sample to the research, has confirmed the search results to own the company's regulatory mechanisms are not required level, has been improved and a number of positive changes, which led to reduce defective rates in the research sample products, and improve the level of quality, as well as increased external customer satisfaction rates, and this leads to the conclusion that the company has achieved aside the mechanics of organizational agility, but not at the required level, as the company continues to operate at rates defective 3%, and the emergence of defective rates after the arrival of the product the customer, has recommended search the adoption of the company's model is a conceptual proposal in order to ensure that the renewable requirements of customers, and rapid response to internal and external change.